agCelerant: world's first fully automated processing system providing concurrent detection of field-level agricultural events, monitoring of crop response, and production forecasts from combined field mobile, IoT and EO data streams - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The integration of EO and IoT into agCelerant was selected by the European Commission's Innovation Radar and rated "Market-Ready" and "Noteworthy for Market Creation Potential". agCelerant and its underpinning concept of phygital agriculture were adopted by IsDB, GIZ, governmental entities and private sector in Benin, Niger, Nigeria, Senegal.